Structure-property relations of co-doped bismuth layer-structured Bi3.25La0.75(Ti1-xMox)3O12 ceramics - Siriprapa P. (2014)
ABSTRACT: In this work, the fabrication and investigation of substituting higher-valence Mo6+ for Ti4+ ion on the B-site of La3+-doped Bi4Ti3O12 [BLT] structure to form Bi3.25La0.75(Ti1-xMox)3O12 [BLTM] (when x = 0, 0.01, 0.03, 0.05 0.07, 0.09, and 0.10) ceramics were carried out. X-ray diffraction patterns of BLTM ceramics indicated an orthorhombic structure with lattice distortion, especially with a higher concentration of a MoO3 dopant. Microstructural investigation showed that all ceramics composed mainly of plate-like grains. An increase in MoO3 doping content increased the length and thickness of the grain but reduced the density of the ceramics. Electrical conductivity was found to decrease, while the dielectric constant increased with Mo6+ doping concentration. Ferroelectric properties were found to be improved with increasing MoO3 content and were optimized at x = 0.1.